Palliative care in gynaecological oncology. Issue 3 (March 2021) - Holmes, Claire; Mitchell, Alison; Downham, Esther
Abstract: Women with a gynaecological malignancy often suffer significant symptom burden, both physically and psychologically, throughout the course of their disease. Despite advances in treatment, up to 25% of women diagnosed with a gynaecological malignancy will die from recurrent disease. Early palliative care involvement provides a holistic approach to care with the benefit of improving symptom control and quality of life for the patient and their carers, as well as lowering resource utilisation at the end of life. Palliative care can be offered alongside curative or life prolonging treatment as well as at end of life. This article reviews the management of common physical symptoms and complications experienced by patients with advanced gynaecological malignancy.